Reelin Alterations, Behavioral Phenotypes, and Brain Anomalies in Schizophrenia: A Systematic Review of Insights From Rodent Models - Sánchez-Hidalgo, Ana C.; Martín-Cuevas, Celia; Crespo-Facorro, Benedicto; Garrido-Torres, Nathalia (Frontiers in Neuroanatomy, 2022)
Reelin is an extracellular matrix glycoprotein reduced in brain regions (prefrontal cortex and hippocampus) of schizophrenia patients. There are diverse animal models of schizophrenia that mimic patient symptoms based on various causal theories, however, likely shared reelin alterations have not yet been systematically assessed in those models. A systematic review of the literature was conducted following the PRISMA model. Articles focused on psychotic disorders or schizophrenia and their relationship with reelin in animal models. The first author, year and results, open field and prepulse inhibition tests results and type of reelin alteration were extracted in duplicate. The 37 articles reviewed reported on various schizophrenia models and their reelin alterations, brain morphology and behavioral defects. We conclude that reelin is an altered preclinical biomarker common to all models included, mainly prenatal or genetic models, and a key protein in schizophrenia disease, making the reelin signaling pathway in prenatal stages a target of special interest for future preclinical and clinical studies. All models presented at least one of the four described reelin alterations types.